1995
DOI: 10.1103/physrevlett.74.142
|View full text |Cite
|
Sign up to set email alerts
|

Simple Model for the Phase Coexistence and Electrical Conductivity of Alkali Fluids

Abstract: We report the first theoretical model for the alkali fluids which yields a liquid-vapor phase coexistence with the experimentally observed features and electrical conductivity estimates which are also in accord with observations.We have carried out a Monte Carlo simulation for a lattice gas model which allows an integrated study of the structural, thermodynamic, and electronic properties of metal-atom fluids. Although such a technique is applicable to both metallic and nonmetallic fluids, non-additive interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
6
21
2
Order By: Relevance
“…It was only with very high precision experiments that it was possible to reveal the singularities in Ne, N 2 , C 2 H 4 , and C 2 H 6 . It was found that the predicted singular behaviour does indeed exist for nonconducting molecular fluids with the critical exponent (1 − α) [17]. The observation of large-diameter anomalies in cesium and rubidium is a most remarkable result.…”
Section: Bulk Critical Phenomenamentioning
confidence: 80%
See 2 more Smart Citations
“…It was only with very high precision experiments that it was possible to reveal the singularities in Ne, N 2 , C 2 H 4 , and C 2 H 6 . It was found that the predicted singular behaviour does indeed exist for nonconducting molecular fluids with the critical exponent (1 − α) [17]. The observation of large-diameter anomalies in cesium and rubidium is a most remarkable result.…”
Section: Bulk Critical Phenomenamentioning
confidence: 80%
“…In all these models a central role is played by the assumption that the intermolecular potentials are functions of thermodynamic variables. For molecular fluids, it was suggested that the physical origin of the state dependence leading to the anomaly is the three-body interaction [17]. There is a natural connection between this explanation and the observation of large amplitude diameter anomalies in cesium, rubidium, and mercury.…”
Section: Bulk Critical Phenomenamentioning
confidence: 94%
See 1 more Smart Citation
“…3) [8]; in constrast with the 'local' conductivities which hardly change. Specially in the vapor branch, it is quite inaccurate to estimate the 'mesoscopic' conductivities assuming uncorrelated ionic positions, or those which are only short-range correlated as hard-sphere (HS).…”
Section: Electrical Conductivitymentioning
confidence: 93%
“…Thus, this is a closed system with the distribution of site occupations and the electronic free en-ergy requiring self-consistent determination for each set of thermodynamic conditions. It seems reasonable to attempt a description of the electronic free energy (3) for each value of T , and representative ensembles of site occupations, as a function of the nn environments of the occupied sites [7,8]. Thus, we try a least-squares fit, to such ensembles of realizations, with a trial form:…”
Section: 2monte Carlo Simulationmentioning
confidence: 99%